2004
DOI: 10.1093/jee/97.3.934
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Transport of Boll Weevils (Coleoptera: Curculionidae) to the Cotton Gin within Cotton Modules

Abstract: There is concern that cotton gins located in boll weevil, Anthonomus grandis grandisBoheman, eradication zones serving customers in adjacent infested zones may serve as a site for boll weevil reintroductions if weevils are transported alive inside cotton modules. We surveyed fields in three distinct areas of Texas and found that weevils can be present in large numbers in cotton fields that have been defoliated and desiccated in preparation for harvest, both as free adults and as immatures inside unopened bolls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…During peak harvest, it is common for modules to remain in the Þeld for 1 to 2 d and in the gin yard for up to a week. Sappington et al (2004d) found that live boll weevils are packed alive into cotton modules, sometimes in large numbers. Those packed on or near the surface can be considered potential dispersants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During peak harvest, it is common for modules to remain in the Þeld for 1 to 2 d and in the gin yard for up to a week. Sappington et al (2004d) found that live boll weevils are packed alive into cotton modules, sometimes in large numbers. Those packed on or near the surface can be considered potential dispersants.…”
Section: Discussionmentioning
confidence: 99%
“…A proportion of the total boll weevils picked up by the harvester are predicted to occur by chance on or near the surface of a module after its construction. Data from our previous survey suggested that Þve to 100 boll weevils were packed within 1 cm of the surface of the cotton modules constructed in the infested Þelds examined (Sappington et al 2004d). These represent potential dispersants at the site of construction, during transport to the gin, or after deposit of the module at the gin yard.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…There is concern that gins operating in areas where boll weevil populations have been eradicated or greatly suppressed may act as sites of reinfestation when serving customers who harvest cotton in a nearby area where weevil populations are still high. Sappington et al (2004a) demonstrated that adult boll weevils are commonly packed alive into modules, which are large free-standing stacks of cotton used to store the harvested cotton until the gin is ready to process it (Lalor et al 1994). In addition, stripperharvested cotton can contain many green bolls (Laird et al 1994), which are sometimes heavily infested with boll weevil larvae, pupae, and unemerged teneral adults (Sappington et al 2004a).…”
mentioning
confidence: 99%
“…Sappington et al (2004a) demonstrated that adult boll weevils are commonly packed alive into modules, which are large free-standing stacks of cotton used to store the harvested cotton until the gin is ready to process it (Lalor et al 1994). In addition, stripperharvested cotton can contain many green bolls (Laird et al 1994), which are sometimes heavily infested with boll weevil larvae, pupae, and unemerged teneral adults (Sappington et al 2004a). Even picker-harvested cotton can contain a small number of green bolls (T.W.S., unpublished data).…”
mentioning
confidence: 99%